Inventing better schools : an action plan for educational reform / Phillip C. Schlechty. - Schlechty, Phillip C., 1937- (Jossey-Bass, 2001)
Building on the strategic framework for school reform outlined in his first book, Schools for the 21st Century, Phillip Schlechty presents an action plan in this book for implementing those reforms.